Estrategias didácticas mediante el uso de scribd para fomentar la autonomía lectora de los estudiantes del subnivel de básica superior. - Saltos Rivera, Nathaly Maricela (2025)
This study explores the implementation of Scribd-mediated teaching strategies to enhance reading autonomy in eighth-grade students at the Upper Basic level. It focuses on fostering critical thinking and meaningful learning by facilitating the selection, analysis, and evaluation of texts. This approach transforms passive reading into an active and conscious process through the use of Scribd, employing educational tactics that influence perceptions of reading proficiency and the willingness to construct knowledge. It also analyzes the challenges and opportunities that the integration of digital technologies presents for the development of reading autonomy in the classroom. The research used a mixed-method approach; the design was cross-sectional and analytical, and the observational method was applied; a structured 15-question survey using Likert scales was administered; the sample consisted of 53 students to obtain their perceptions regarding the use of digital platforms that promote reading and thus obtain an initial diagnosis; the data were processed in Excel using frequencies and percentages and are presented in tables and figures; teachers were interviewed using a semi-structured script. The results suggest an increase in students' confidence in selecting and addressing diverse texts, as well as an improvement in their ability to discern relevant information and make critical judgments. There was evidence of a greater willingness to explore materials outside the traditional curriculum, indicating a strengthening of their autonomy. Challenges included connectivity and equitable access to devices, while opportunities lie in personalized learning. The findings provide guidelines for the design of future educational interventions that empower students as autonomous readers, capable of effectively using digital resources to expand their reading and learning horizons.